THE EFFECTIVENESS OF DEEP LEARNING-BASED LEARNING WITH A PROJECT-BASED LEARNING MODEL TO IMPROVE STUDENT LEARNING OUTCOMES IN REGIONAL DEVELOPMENT MATERIALS AT SMA NEGERI 4 JAYAPURA CITY - Tommi; Poppy Haryani; Inriyatni Sri Pertiwi Ginting; Renny T. Tumober; Muhammad Ridwan; Febriyanti Angelia Ginting (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study analyzes the effectiveness of integrating Deep Learning and Project-Based Learning (PjBL) on student learning outcomes in Regional Development material at SMA Negeri 4 Kota Jayapura. A quasi-experimental method with one group pretest-posttest design was applied to 34 students of class XI D. Data were collected through tests, observations, and documentation, then analyzed using Paired Sample t-Test. The results showed a significant increase in learning outcomes with pretest average of 24.29 to 74.96 in posttest (t = -29.717; p < 0.05). This learning also produced contextual teaching materials and improved students' conceptual understanding from memorization to analytical thinking. This study contributes to the development of innovative geography learning models. Future research is recommended to use control groups and integrate digital technology.